Empowering Doctors: Mastering the Legal Dimensions of Medical Consultation for Better Practice - Fakih, M.; Natamiharja, Rudi; Setiawan, Ikhsan (Probono and Community Service Journal, 2024)
This service addresses the growing need for medical professionals to understand the legal dimensions of healthcare. With the increasing complexity of legal challenges in medical practice, this initiative offers socialization and training to enhance doctors' awareness of crucial legal concepts, such as patient rights, medical obligations, and data protection. By utilizing a participatory, interactive approach, the training incorporates real-world cases to bridge theoretical knowledge with practical application. The results demonstrate a significant increase in medical staff confidence, equipping them to navigate legal requirements and safeguard patient rights in an increasingly regulated healthcare environment. This research contributes to addressing the urgent need for legal literacy among medical professionals to ensure both ethical and compliant practice